2002
DOI: 10.1067/mtc.2002.121506
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass: Evidence or experience based?

Abstract: The scientific data concerning the effectiveness and safety of key principles of cardiopulmonary bypass are insufficient in both amount and quality of scientific evidence to serve as a basis for practical, evidence-based guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…In addition, urine fl ow as an indicator of renal function during operation was positively correlated to mean arterial pressure on cardiopulmonary bypass, but there was no effect on postoperative renal function [22,23] . As recent studies have demonstrated that cardiopulmonary bypass management is not evidence based [24] , our current clinical pulsatile perfusion practice may favor renal dysfunction. Therefore, the purpose of our study was to investigate whether clinical routine pulsatile fl ow management infl uences postcardiac surgery renal function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, urine fl ow as an indicator of renal function during operation was positively correlated to mean arterial pressure on cardiopulmonary bypass, but there was no effect on postoperative renal function [22,23] . As recent studies have demonstrated that cardiopulmonary bypass management is not evidence based [24] , our current clinical pulsatile perfusion practice may favor renal dysfunction. Therefore, the purpose of our study was to investigate whether clinical routine pulsatile fl ow management infl uences postcardiac surgery renal function.…”
Section: Introductionmentioning
confidence: 99%
“…5 In this setting, the development of scoring systems, such as the QualyP Score, might represent an advantage and a first step towards the definition of goal-directed perfusion strategies and quality benchmarking.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, several surveys proved that the scientific data available at present are not yet sufficient to serve as evidence-based guidelines. 5,6 The present study aims to evaluate the quality of organ perfusion during CPB and to structure a scoring system to assess The aim of this study was to ascertain if a score, directly derived from CPB records, could correlate to major postoperative outcomes. Methods: An additive score (QualyPscore) was created from 10 parameters: peak lactate value during CPB, peak VCO 2 i, lowest DO 2 i/VCO 2 i, peak respiratory quotient, CPB time, cross-clamp time, lowest CPB temperature, circulatory arrest, ultrafiltration during CPB, number of packed red cells transfused intraoperatively.…”
mentioning
confidence: 99%
“…The promotion of neutropenia by leukocyte depletion filter (LDF) [11] and radiation [39], the association between NO and hypothermia during CPB reducing the adherence of leukocytes to the endothelium [40], the modifications of the cardioplegic solution [41], heparinization of the surface of the CPB system, the addition of anti-inflammatory and chelating agents of OFR to the circuit [4.42 to 44], were not sufficient to reduce inflammatory markers in the postoperative period and to support the standardization of with any of these alternatives to the procedure of CPB [45].…”
Section: Attenuation Of the Inflammatory Response: Actions On Neutropmentioning
confidence: 99%